American frontier myth and black humour: a study of Marsha Norman’s The Holdup - Jose, Soumya; Raj, Sony Jalarajan (My University, 2017)
American frontier myth, which can aptly be termed as a relic of the past is intricately woven into the plot of Marsha Norman’s play, The Holdup. This paper attempts to unravel how the playwright has employed black humour to stage the metamorphosis of a naïve teenager to an adult with broader world view. Besides, the paper examines the technique of meta-narration used by the playwright to narrate the events that had happened offstage.
Keywords: American frontier myth; outlaws; black humour; meta-narration; transformation